2016
DOI: 10.2169/internalmedicine.55.4655
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammatory Syndrome Associated with a Case of Jugular Paraganglioma

Abstract: Jugular paraganlioma is a benign, slow-growing tumor originating from the paraganglion cells and it is associated with catecholamine secretion. Paragangliomas can secrete Interleukin-6 (IL-6) and present as a systemic inflammatory syndrome; these characteristics have not been previously associated with jugular paragangliomas. A 63-year-old man with a jugular tumor in the skull base was referred to our hospital for an evaluation of pyrexia, back pain, and acute inflammation. His serum IL-6 level was elevated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…(13,14) The classic signaling of this cytokine starts with the binding to its membrane receptor (IL-6R), which leads to the activation of the intracellular signaling pathway of the Janus kinases. Subsequently, signal transduction-activated transcription factors translocate into the nucleus and gene expression is induced, as in the case of pro-opiomelanocortin (POMC), (15,16) which then generates ACTH by cleavage. In this way, it is possible to explain ACTH-dependent hypercortisolism, which was one of the biochemical alterations presented by the reported patient.…”
Section: Discussionmentioning
confidence: 99%
“…(13,14) The classic signaling of this cytokine starts with the binding to its membrane receptor (IL-6R), which leads to the activation of the intracellular signaling pathway of the Janus kinases. Subsequently, signal transduction-activated transcription factors translocate into the nucleus and gene expression is induced, as in the case of pro-opiomelanocortin (POMC), (15,16) which then generates ACTH by cleavage. In this way, it is possible to explain ACTH-dependent hypercortisolism, which was one of the biochemical alterations presented by the reported patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature reports only limited cases of IL-6 over-production in paraganglioma. Sokabe et al reported a case in a patient with the systemic inflammatory syndrome, having increased IL-6 level due to a jugular paraganglioma, without any detectable hormone secretion including catecholamines (20). Another case report in the literature presented the coexistence of Castleman disease and pheochromocytoma possibly by linking up to the expression of IL-6 by the tumor mass (17).…”
Section: Discussionmentioning
confidence: 99%
“…Mass effect on facial nerve can lead to subclinical facial asymmetry, laterality of proprioception in the orofacial muscles and TMJ dysfunction [6]. Paraganglioma rarely secrete various neuropeptide hormones, such as adrenocorticotropic hormone, and inflammatory cytokines, such as interleukin-6 (IL-6) inducing acute inflammatory reaction and pain [7].…”
Section: Discussionmentioning
confidence: 99%